P38 MAPK Contributes to Resistance and Invasiveness of HER2- Overexpressing Breast Cancer - Donnelly, S.M.; Paplomata, E.; Peake, B.M.; Sanabria, E.; Chen, Z.; Nahta, R. (Current Medicinal Chemistry, 2014)
Intrinsic or acquired resistance to the HER2-targeted therapy trastuzumab is a clinical concern in the treatment of patients with HER2-over-expressing metastatic breast cancers. We demonstrate here that multiple models of intrinsic and acquired resistance exhibit increased phosphorylation of p38 MAPK. Kinase inhibition of p38 rescued trastuzumab sensitivity in cells with acquired resistance. In addition, knockdown of p38 increased sensitivity to trastuzumab in an intrinsically resistant cell line. We previously reported that expression of growth differentiation factor 15 (GDF15) is increased in trastuzumab-resistant HER2-overexpressing breast cancer cells. In this study, we found that exogenous GDF15 or stable overexpression of GDF15 stimulated p38 phosphorylation in HER2-positive cells, suggesting a possible mechanism by which p38 is activated in resistant cells.GDF15 stable clones showed significantly increased invasiveness, which was rescued by p38 kinase inhibition, suggesting that p38 plays a role in the pro-invasive phenotype conferred by GDF15. Importantly, immunohistochemical analysis of a breast tumor tissue array indicated a significant (p=0.0053) correlation between HER2 and phosphorylated p38 specifically in GDF15-positive tissues. Our results suggest that p38 signaling drives trastuzumab resistance and invasiveness in HER2-overexpressing breast cancer. Upstream growth factor signals that have previously been implicated in trastuzumab resistance, such as GDF15, may contribute to the increased phosphorylation of p38 found in resistant cells.
Keywords: HER2